Distributed opportunistic spectrum sharing in cognitive radio networks. (19th May 2016) - Hawa, Mohammed; AlAmmouri, Ahmad; Alhiary, Ala; Alhamad, Nidal
Summary: In cases where the licensed radio spectrum is underutilized, cognitive radio technology enables cognitive devices to sense and then dynamically access this scarce resource making the most out of it. In this work, we introduce a simple and intuitive, yet powerful and efficient, technique that allows opportunistic channel access in cognitive radio systems in a completely distributed fashion. Our proposed method achieves very high values of spectrum utilization and throughput. It also minimizes interference between cognitive base stations and the primary users licensed to use the spectrum. The algorithm responds quickly and efficiently to variations in the network parameters and also achieves a high degree of fairness between cognitive base stations. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A simple and powerful opportunistic channel access technique for cognitive radio systems is presented. This technique achieves very high values of spectrum utilization and throughput and responds quickly and efficiently to variations in the network parameters.